Sulfur Dioxide Effects on Human Atrial Action Potential: In Silico Study (2018)
Exposure to air pollutants agents, like sulfur dioxide (SO2), has significant effects on the cardiovascular system. Studies have shown that SO2 blocks ICaL and increases the INa, IK1 and Ito currents, which implies action potential duration (APD) decrease, favoring the initiation of atrial arrhythmias. This study aims to assess the effects of the SO2 at different concentrations on human atrial action potential, using computational simulation. For this, based on experimental data, we developed concentration-dependent equations to simulate the SO2 effects on the currents. They were incorporated in the Courtemanche model of human atrial cell and in a 2D model of atrial tissue. S1-S2 cross-field protocol was applied to initiate a rotor. SO2 concentrations from 0 to 100 ? M were implemented. Our results are in agreement with results from non-human in vitro and in vivo studies. The SO2 causes APD shortening and loss of plateau phase in a fraction that increases as the concentration increases. In the 2D model, a rotor can be generated from 50 ? M of SO2 concentration, showing a pro-arrhythmic effect. © 2018 Creative Commons Attribution.